Teenagers’ Well-Being through Family Leisure Activities - Ayudhia Fachrandini; Zulfa Febriani (Universitas Muhammadiyah Surakarta, 2023)
The rise in mental health issues and suicide rates among adolescents in Indonesia emphasizes the significance of prioritizing adolescent mental health. One key contributor to mental health issues and suicide among adolescents is the family unit. The psychological well-being of adolescents is linked to the dynamics of dual-earner families. The study seeks the correlation between family engagement in leisure activities and adolescents' psychological well-being from dual-income households in Indonesia. The research method employed is correlational. The study cohort comprises 173 adolescents from dual-income households selected through accidental sampling. Family Leisure Activity Profile (FLAP) and Ryff's Psychological Well-being Scale (RPWBS) measured family participation in leisure activities and subsequent psychological well-being. The results of the Spearman-rank correlation test revealed a significant positive association between family engagement in leisure activities and psychological well-being dimensions such as autonomy, environmental mastery, positive relationships with others, purpose in life, and self-acceptance (rs= 0.237-0.294, p< 0.01). The results also showed no correlation between family involvement in leisure activities and personal growth (rs= 0.880, p= 0.295). Therefore, increased family involvement in leisure time corresponds to enhanced psychological well-being for adolescents in dual-earner families. Parents who work should organize routine activities and leisure time with their teenagers, which promote self-expression, values transfer, and improved family members’ psychological well-being.